Comparative methylomics reveals gene-body H3K36me3 in Drosophila predicts DNA methylation and CpG landscapes in other invertebrates - Nanty, Lisa (Cold Spring Harbor Laboratory Press, 2011)
In invertebrates that harbor functional DNA methylation enzymatic machinery, gene-bodies are the primary targets for CpG methylation. However, virtually all other aspects of invertebrate DNA methylation have remained a mystery until now. Here, using a comparative methylomics approach, we demonstrate that Nematostella vectensis, Ciona intestinalis, Apis mellifera, and Bombyx mori show two distinct populations of genes differentiated by gene-body CpG density. Genome-scale DNA methylation profiles for A. mellifera spermatozoa reveal CpG-poor genes are methylated in the germline, as predicted by the depletion of CpGs. We find an evolutionarily conserved distinction between CpG-poor and GpC-rich genes: The former are associated with basic biological processes, the latter with more specialized functions. This distinction is strikingly similar to that recently observed between euchromatin-associated genes in Drosophila that contain intragenic histone 3 lysine 36 trimethylation (H3K36me3) and those that do not, even though Drosophila does not display CpG density bimodality or methylation. We confirm that a significant number of CpG-poor genes in N. vectensis, C. intestinalis, A. mellifera, and B. mori are orthologs of H3K36me3-rich genes in Drosophila. We propose that over evolutionary time, gene-body H3K36me3 has influenced gene-body DNA methylation levels and, consequently, the gene-body CpG density bimodality characteristic of invertebrates that harbor CpG methylation.